IgY-based antivenom against Bothrops alternatus: Production and neutralization efficacy - Leiva, Carlos Leónidas (2019)
Antivenom for the treatment of bothropic snakebite is a priority for public health institutions from Latin America. An alternative to the conventional antivenom production is based on the use of egg yolk antibodies – IgY-technology – by immunizing laying hens. In this study, we produced, characterized and assessed the efficacy of IgY-based antivenoms against B. alternatus venom. Immunochemical studies (reactivity, avidity and antigen recognition pattern) as well as antivenom efficacy assays were performed. After the 3rd immunization, levels of specific IgY reached a maximum that was maintained throughout the observation period, while avidity indexes of the extracts increased after the successive immunizations. Furthermore, IgY against B. alternatus recognized protein complexes of the venom with high (>40 kDa), medium (20–40 kDa) and low (<20 kDa) molecular weights. IgY antivenoms obtained after 8 immunizations neutralized 35.65 μg of B. alternatus venom per mg of antivenom, while specific activities values ranged from 0.28 to 0.42. In conclusion, we produced and characterized IgY antivenoms capable of neutralizing the lethal activity of B. alternatus venom at a preclinical level. Thus, IgY-technology may allow the production of effective and affordable antivenoms fulfilling the urgent needs of many countries where conventional manufacture is unable to provide enough availability of antivenoms.